The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1136/bmjopen-2019-030719
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and beliefs about dietary inorganic nitrate among UK-based nutrition professionals: development and application of the KINDS online questionnaire

Abstract: ObjectivesTo examine knowledge and beliefs about the biological roles of dietary inorganic nitrate in UK-based nutrition professionals, and to explore potential differences by participants’ education level.SettingAn online questionnaire was administered to UK-based nutrition professionals, exploring knowledge and/or beliefs across five areas: (1) health and performance effects of nitrate; (2) current and recommended intake values for nitrate; (3) dietary sources of nitrate; (4) methods of evaluating nitrate in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 41 publications
2
18
2
Order By: Relevance
“…We chose the subjects based on this criterion due to the fact that our survey could only be answered online. In sum, this study is an ICT-based structure, similar to a few other studies [31,63].…”
Section: Discussionsupporting
confidence: 52%
“…We chose the subjects based on this criterion due to the fact that our survey could only be answered online. In sum, this study is an ICT-based structure, similar to a few other studies [31,63].…”
Section: Discussionsupporting
confidence: 52%
“…The initial results suggesting a harmful role of dietary NO 3 − intake (from food) were mostly derived from animal models and weakly designed epidemiological studies which have had a prominent, almost demonizing, influence on defining the role of dietary NO 3 − for human health [ 87 ]. These initial studies informed the still contentious WHO nutritional recommendations for dietary NO 3 − intake in humans which was set at 3.7 mg/ kg body weight [ 88 ]. The perception of dietary NO 3 − as a risk factor started to change with the discovery of the role of NO 3 − as key substrate for the NO 3 − -NO 2 − -NO pathway and the evidence of a beneficial effect of NO 3 − on health parameters such as BP.…”
Section: Main Textmentioning
confidence: 99%
“…NO 3 − is increasingly recognised as a beneficial ion that protects against chronic disease, yet, as noted in Section 3 of this review, historically, it was considered a food contaminant with adverse health effects, particularly increased risk of certain cancers and methaemoglobinaemia [ 1 , 88 ]. While the aforementioned WHO ADI for NO 3 − of 3.7 mg/kg of body mass remain in place today, the discovery of multiple positive health effects of NO 3 − have prompted a re-examination of these claims.…”
Section: Main Textmentioning
confidence: 99%
“…For example, two beetroot juice shots containing a total of 800 mg of inorganic nitrate would provide over three times the ADI of 259 mg/day for a 70-kg individual. The ADI restricting dietary nitrate intake was originally based on observational and animal model data, which suggested that acute or chronic consumption of nitrate could increase the risk of methaemoglobinaemia, whilst chronic nitrate intake could increase risk of cancer [ 27 , 28 ]. Methaemoglobinaemia is a rare condition in which the ferrous iron (Fe 2+ ) in haemoglobin is oxidized into the ferric (Fe 3+ ) state, forming methaemoglobin [ 29 ].…”
Section: Introductionmentioning
confidence: 99%